Recruitment of people with dementia in primary care –experiences from the HIND study - van der Wardt, Veronika; Conroy, Simon; Tomas, W.; Logan, Pip; Harrison, Jennifer K.; Taggar, Jaspal; Gladman, John R.F. (Elsevier, 2015)
OBJECTIVES: A purpose of the Hypertension in Dementia feasibility study was to explore recruitment of people with dementia and essential hypertension in primary care practices to prepare a withdrawal study of their antihypertensive medication. METHODS: Primary care practices were invited by phone to support the study, which would entail screening their databases to identify people with diagnoses of both dementia and essential hypertension, and sending out letters to these people asking them to indicate their willingness participate in the feasibility withdrawal study. Practice managers or GPs from practices that declined to support the study were asked to give their reasons. RESULTS: All primary care practices in Nottingham and Nottinghamshire were contacted (n=145). Of those, 12 (8%) practices agreed to support the study. Between them they identified and sent out a total of 249 letters to potential participants. Of these 19 (7%) people responded and only 6 (2%) met the eligibility criteria for withdrawing antihypertensive medication. 80/133 (60%) non responding practices gave reasons for why they did not support the study: the most common responses were that 31 (39%) were ‘too busy’, staff changes or short staffed were cited in 11 (14%) and “too time consuming” was cited in 7 (9%). CONCLUSIONS: Recruitment of a sufficiently large and representative population for a larger trial would not be feasible in primary care practices using these methods, due to the high workload in UK primary care.